2016
DOI: 10.1016/j.ijchp.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Criteria-Based Content Analysis (CBCA) reality criteria in adults: A meta-analytic review

Abstract: Background/Objective: Criteria-Based Content Analysis (CBCA) is the tool most extensively used worldwide for evaluating the veracity of a testimony. CBCA, initially designed for evaluating the testimonies of victims of child sexual abuse, has been empirically validated. Moreover, CBCA has been generalized to adult populations and other contexts though this generalization has not been endorsed by the scientific literature. Method: Thus, a meta-analysis was performed to assess the Undeutsch Hypothesis and the CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
142
1
21

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(202 citation statements)
references
References 37 publications
20
142
1
21
Order By: Relevance
“…As expected, participants primarily reported nonverbal cues-most notably gaze aversion and nervous behavior-as useful for detecting deception, replicating our previous study (Bogaard et al, 2016), as well as many others (e.g., Akehurst et al, 1996;Masip & Herrero, 2015;Strömwall et al, 2004;Strömwall & Granhag, 2003;Taylor & Hick, 2007;Vrij et al, 2006;Vrij & Semin, 1996). Although verbal signals were reported to a lesser extent, the cues that were reported (i.e., inconsistencies, details, and coherence) were largely supported by empirical research (Amado et al, 2015;Amado, Arce, Fariña, & Vilariño, 2016;Masip et al, 2005;Oberlader et al, 2016;Vrij, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…As expected, participants primarily reported nonverbal cues-most notably gaze aversion and nervous behavior-as useful for detecting deception, replicating our previous study (Bogaard et al, 2016), as well as many others (e.g., Akehurst et al, 1996;Masip & Herrero, 2015;Strömwall et al, 2004;Strömwall & Granhag, 2003;Taylor & Hick, 2007;Vrij et al, 2006;Vrij & Semin, 1996). Although verbal signals were reported to a lesser extent, the cues that were reported (i.e., inconsistencies, details, and coherence) were largely supported by empirical research (Amado et al, 2015;Amado, Arce, Fariña, & Vilariño, 2016;Masip et al, 2005;Oberlader et al, 2016;Vrij, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…For a separate project, I recently collected and reanalyzed the literature from Amado et al (2016;see RabbitSnore, 2018, for a description of how the data were assembled). Their review encompasses literature from 1993 to 2015, and here I examined data for 36 of the studies included in the review that reported individual cues (rather than composites of multiple cues).…”
Section: Trouble In the Land Of Toysmentioning
confidence: 99%
“…Primero, la situación no es real por lo que los participantes no actúan como en tal circunstancia (implicación), con efectos directos en los resultados (validez aparente) en la investigación en psicología forense (Fariña, Real, y Arce, 1994). Al respecto, la literatura ha constatado sistemáticamente (ver revisiones meta-analíticas de menores y adultos; Amado et al, 2015Amado et al, , 2016Oberlader et al, 2016) que la capacidad discriminativa y de clasificación de memorias de hechos auto-experimentados de los criterios de realidad del CBCA es significativamente mayor en estudios de campo (casos reales) que en estudios de laboratorio (casos simulados). Segundo, la longitud de la declaración tiene efectos en la productividad de las categorías de contenido (Arce, 2017;Köhnken, 2004), siendo significativamente menor en las memorias autobiográficas que en las reales de eventos de victimización de un delito, y las fabricadas en condiciones experimentales de las fabricadas con propósitos judiciales.…”
Section: Discussionunclassified
“…Especialmente reseñable es que el criterio auto-desaprobación que había resultado no significativo (esto es, si bien el tamaño del efecto promedio era positivo, el intervalo de confianza para dicho efecto incluía el 0 de modo que en estudios se pueden obtener resultados contrarios a la hipótesis) en la discriminación entre memorias de eventos auto-experimentados y fabricadas en población adulta en el metaanálisis de Amado et al (2016), este resultado avala que este criterio no sólo es efectivo en dicha discriminación (h = 0.93), sino altamente robusto en la correcta clasificación de las memorias autoexperimentadas en relación a las fabricadas visionadas (línea base/grupo control) en vídeo (ΔPCC = .422).…”
Section: Discussionunclassified
See 1 more Smart Citation